Ambiguities of War: A Narratological Commentary on Silius Italicus' Battle of Ticinus (Sil. 4.1-479) - Schedel, Elisabeth, (Mnemosyne, Supplements ;, 2022)
The book lays bare the narrative form of Silius' text. It focuses on the phenomenon of ambiguity due to the epic's constant oscillation between fact and fiction, highlighting Roman triumph in defeat and defeat through triumph.